The Influence of Brand Ambassador on Brand Image with Online Customer Review as Moderation Variable - Nurhikmah; Retno Dewi Wijiastuti; Muhammad Hasan Lubis; Sriwanti Belani; Rini Hadiyati (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
This research is a quantitative study with an explanatory approach, namely an approach that relies on the four studies mentioned above as the main material to be studied so as to produce novelty and new hypotheses that are slightly different from previous studies. The data used in this study are primary data that researchers obtained from Hokben employees spread throughout Indonesia. The data obtained were analyzed using the smart PLS 4.0 analysis tool. The conclusion in this article show that all hypotheses used in this study, both the first and second, can be accepted and proven. The first hypothesis in this study is that the Brand Ambassador variable can have a positive relationship and a significant influence on Brand Image. This hypothesis can be accepted because the P-Values ​​are positive and below the significance level of 0.05, namely 0.007. These results indicate that the better the Brand Ambassador used by a company in marketing its products, the better the company's Brand Image will be. The second hypothesis used in this study is that the Online Customer Review variable can moderate the influence of the Brand Ambassador variable on the Brand Image variable. From the results of the third table above, it can be shown that the hypothesis can be accepted because the P-Values ​​are positive and are below the significance level of 0.05, namely 0.000, which is more significant than direct testing of 0.007. Thus, it can be concluded that the first and second hypotheses in this study can be accepted and proven